2020
DOI: 10.1097/j.pain.0000000000001808
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun/p38MAPK/ASIC3 pathways specifically activated by nerve growth factor through TrkA are crucial for mechanical allodynia development

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
(71 reference statements)
2
19
0
Order By: Relevance
“…Further mechanistic study revealed that NGF upregulated the expression of ASIC3 through c-jun/p38MAPK pathway and that ASIC3 was crucial for the development of NGF-induced mechanical hyperalgesia. 37 Consistent with their studies, we found that ASIC3 agonist recapitulated tooth mechanical hyperalgesia that was attenuated by periodontal administration of anti-NGF neutralizing antibody. Moreover, our results revealed that ASIC3 antagonist could attenuate tooth mechanical hyperalgesia that was aggravated by periodontal administration of NGF.…”
Section: Discussionsupporting
confidence: 91%
“…Further mechanistic study revealed that NGF upregulated the expression of ASIC3 through c-jun/p38MAPK pathway and that ASIC3 was crucial for the development of NGF-induced mechanical hyperalgesia. 37 Consistent with their studies, we found that ASIC3 agonist recapitulated tooth mechanical hyperalgesia that was attenuated by periodontal administration of anti-NGF neutralizing antibody. Moreover, our results revealed that ASIC3 antagonist could attenuate tooth mechanical hyperalgesia that was aggravated by periodontal administration of NGF.…”
Section: Discussionsupporting
confidence: 91%
“… 5 , 25 , 60 Recent hypothesis-driven studies investigated mRNA levels in the skin, DRG, and spinal dorsal horn after incision in rodents and discovered multiple mediators to be regulated. 13 , 48 , 57 , 65 However, transcript levels correlate only up to 50% with factual levels of corresponding proteins, which renders the interpretation of RNA-based results and identification of novel targets are challenging. 44 Hence, a thorough understanding of incision-induced dynamics warrants the inclusion of comprehensive studies at the proteome level.…”
Section: Introductionmentioning
confidence: 99%
“…Several pain-related signaling pathway targeting ASICs have been previously characterized, including PKC (Baron et al, 2002), PKA (Leonard et al, 2003) or phosphoinositide 3-kinase (PI3K)-protein kinase B (PKB/Akt) (Duan et al, 2012). A MAPK-dependent transcriptional regulation of ASIC3 has been involved in the effect of NGF (Mamet et al, 2003; Chaumette et al, 2020) or interleukin 1β (Ross et al, 2016), and a MAPK-dependent transcriptional regulation of ASIC1a has also been associated to the effect of interleukin 6 (Zhou et al, 2015) or oxidative stress (Wu et al, 2020), but a MAPK-dependent phosphorylation of ASIC channels has never been described so far. Our data are consistent with a phosphorylation by JNK of the ASIC1b and ASIC3 (except mouse ASIC3) subunits.…”
Section: Discussionmentioning
confidence: 99%